2020
DOI: 10.1002/adfm.202004417
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Gradient‐Based Soft Robotics: Hydrogels Out of Water

Abstract: Hydrogels are biocompatible soft materials that resemble biological tissues more than any other material. However, the use of these systems in soft robotics has been limited to aqueous environments. In the work published to date, hydrogels have relied on external water to swell or shrink in response to stimuli and, therefore, to actuate macroscopically. In the work reported here, this limitation is overcome by synthesizing a novel type of electroactive hydrogels capable of actuating when a low electric field i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…Next, we demonstrate that a single GO mesotube can be used as a multifunctional sensor for perceiving vibration, temperature, and human artery pulse pressure. Because the GO mesotubes operate as a sensor in wet conditions, they are highly likely to be used as soft robotics [26][27][28][29] or electronic skin. [30][31][32][33] Recently, flexible, affordable, and elastic wearable electronics have been highlighted for monitoring human biomedical signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we demonstrate that a single GO mesotube can be used as a multifunctional sensor for perceiving vibration, temperature, and human artery pulse pressure. Because the GO mesotubes operate as a sensor in wet conditions, they are highly likely to be used as soft robotics [26][27][28][29] or electronic skin. [30][31][32][33] Recently, flexible, affordable, and elastic wearable electronics have been highlighted for monitoring human biomedical signals.…”
Section: Resultsmentioning
confidence: 99%
“…The GO mesotubes behaved like a soft gel with a Young's modulus of 974 Pa and were robust to 10 5 cycles of bending tests, rendering them promising candidates as wet sensors for soft robotics [26][27][28][29] and electronic skins. [30][31][32][33] As a proof of concept, we demonstrated that a single GO mesotube can be used as a wet-conditioned sensor for monitoring mechanical vibration and human artery pulse pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ionogels and polymer electrolyte hydrogels can also be used as the polymer component of IPMC. The performance of hydrogel-based IPMC tend to suffer from drying out effects, but are promising from an ease of fabrication and bio-compatibility perspective [84]. Ionogelbased IPMC do not suffer from drying out and are less susceptible to back relaxation than ionomers in IPMC, but do tend to be less stiff and strong than ionomers [85][86][87][88][89].…”
Section: Swelling Sensors and Actuatorsmentioning
confidence: 99%
“…With the explosive progress of artificial intelligence and the internet of things, considerable efforts have been contributed to explore novel materials for next‐generation integrated touch panels with multifunctionalities such as transparency, stretchability, flexibility, and self‐healing capability because the traditional touch panels based on indium tin oxide face various limitations due to its brittle and stiff nature. [ 1–6 ] Among them, hydrogels have received great attention in the development of emerging fields ranging from tactile sensors, [ 7 ] human‐machine interfaces, [ 8 ] and soft robotics [ 9 ] to energy harvesting/storage devices [ 10–13 ] due to their multiple functions, stretchability, biocompatibility, and conductivity. [ 14–17 ] Therefore, hydrogels are considered as a promising candidate for the new‐generation human‐machine interactive touch panel.…”
Section: Introductionmentioning
confidence: 99%
“…touch panels based on indium tin oxide face various limitations due to its brittle and stiff nature. [1][2][3][4][5][6] Among them, hydrogels have received great attention in the development of emerging fields ranging from tactile sensors, [7] human-machine interfaces, [8] and soft robotics [9] to energy harvesting/storage devices [10][11][12][13] due to their multiple functions, stretchability, biocompatibility, and conductivity. [14][15][16][17] Therefore, hydrogels are considered as a promising candidate for the new-generation humanmachine interactive touch panel.…”
mentioning
confidence: 99%